Do geologic hazards affect the sustainability of rural development? Evidence from rural areas in China. (10th March 2022) - Gan, Lu; Wang, Li; Hu, Zhineng; Lev, Benjamin; Gang, Jun; Lan, Hongxing
Abstract: Recently, rural depopulation and environmental damage caused by natural disasters have seriously affected sustainable rural development (SRD). Sustainable consumption and production (SCP), as the focus of sustainable development goals (SDGs), plays a critical role in agricultural development and rural economy. To determine whether geological hazards have an impact on rural development, this study developed a two-stage parallel-series network DEA model for assessing the sustainability of high-, medium-, and low-risk areas. The model combined radial and non-radial measurements to account for the non-proportional changes in inputs and outputs. Due to the fuzziness of loss magnitude and the randomness of disaster frequency, fuzzy random variables were employed to characterize economic losses. The model was applied to a case study in high-altitude rural mountainous areas of southwest China during 2016 to 2018. It was found that the impact of geological hazards on SRD was spatially heterogeneous; that is, the degree of impact depends on the socioeconomic development rather than risk magnitude. Assessing the sustainability of SRD required complete identification and classification of area types. In addition, geological hazards would seriously affect the sustainability of the rural areas, especially in areas with less developed transportation and remote terrain. Compared with the sustainable production (SP) stage, the sustainable consumption (SC) stage could generate more economic value. Highlights: A two-stage parallel-series network DEA is developed to assess sustainability. The model allows for evaluating the sustainable production and consumption stages. The fuzzy random variables are employed to characterize the economic loss. The impact of geologic hazards on SRD shows spatial heterogeneity. The SC stage generates greater economic values than the SP stage.